Design of a Reconfigurable Pulsed Quad-Cell for Cellular-Automata-Based Conformal Computing. (8th July 2010) - Hoseini, Mariam; Tan, Zhou; You, Chao; Pavicic, Mark
Abstract : This paper presents the design of a reconfigurable asynchronous computing element, called the pulsed quad-cell (PQ-cell), for constructing conformal computers. Conformal computers are systems with an exceptional ability to conform to the physical and computational needs of an application. PQ-cells, like cellular automata, are assembled into arrays, communicate with neighboring cells, and are collectively capable of general computation. They operate asynchronously to scale without the limitations of a global clock and to minimize power consumption. Cell operations are stimulated by pulses which travel on different wires to represent 0's and 1's. Cells are individually configured to perform logic, move and store information, and coordinate parallel activity. The PQ-cell design targets a 0.25 μ m CMOS technology. Simulations show that a single cell consumes 15.6 pJ per operation when pulsed at 1.3 GHz. Examples of multicell structures include a 98 MHz ring oscillator and a 190 MHz pipeline.